Entecavir Allows an Unexpectedly High Residual Replication of HBV Mutants Resistant to Lamivudine. Issue 8 (November 2015) - Geipel, Andreas; Seiz, Pia L; Niekamp, Hauke; Neumann-Fraune, Maria; Zhang, Ke; Kaiser, Rolf; Protzer, Ulrike; Gerlich, Wolfram H; Glebe, Dieter; ,
Background: Entecavir is an efficient inhibitor of HBV reverse transcriptase (RT) and widely used for therapy of chronic hepatitis B. Entecavir treatment of HBV patients with lamivudine-resistant viral strains, however, often fails, but the mechanism of cross-resistance development is not fully understood. Methods: Using non-linear regression models, dose– response curves of cloned HBV strains from patients pre-treated with RT inhibitors were established in human hepatoma cell lines after transfection with HBV genomes containing HBV polymerase genes from patient isolates. 50% and 90% inhibitory concentrations (IC50 and IC90 ) and corresponding antiviral resistance factors (RF50 and RF90 ) were calculated. Results: The entecavir dose–response curve of lamivudine-resistant HBV RT mutants rtM204 for the replication of HBV decreased less than expected with increasing drug dose. Remarkably, due to the fat dose–response curves, RF90 values against entecavir of samples with rtM204 substitutions were up to 30 xhigher than their RF50 values. Conclusions: The unexpectedly high IC90 indicates a strong residual replication capacity of lamivudine-resistant HBV rtM204 variants under entecavir therapy, although IC50 values are initially within the therapeutic range of ente-cavir. This characteristic favours rapid selection of additional mutants with overt resistance against entecavir. Thus, the current phenotypic resistance assays should include determination of IC90 .